Solid-phase synthesis of the lipopeptide Myr-HBVpreS/2-78, a hepatitis B virus entry inhibitor - Schieck, Alexa; Müller, Thomas; Schulze, Andreas; Haberkorn, Uwe; Urban, Stephan; Mier, Walter (Molecules, 2010)
Chronic HBV infection is the leading cause of liver cirrhosis and hepatocellular carcinoma (HCC). Synthetic peptides derived from the N-terminus of the large HBV envelope protein (L-protein) have been shown to efficiently block HBV entry. Myr-HBVpreS/2-78, the parent compound of these drugs, inhibits human HBV infection in vitro and in vivo. An efficient synthesis is required, as these peptides constitute a novel class of anti HBV drugs. Consequently, the solid phase synthesis of the N-terminal 77 amino acids of the viral L-protein was studied in detail. The peptide was N-terminally myristoylated to resemble the natural, postranslationally modified protein. The synthesis was monitored using the Fmoc cleavage pattern of the solid phase synthesis on a standard peptide synthesizer and by LC-MS analyses of the arising side products. “Difficult sequences” in the positions 42-47 of the peptide sequence complicate the efficient synthesis of the 77-mer peptide HBVpreS/2-78. Attempts were undertaken to optimize the synthesis by heating, double coupling or the use of pseudoproline dipeptides. HPLC-MS analyses showed that the efficiency of the synthesis could be increased best by temperature elevation. This resulted in a higher purity of the crude product after solid phase synthesis. It was possible to minimize the occurrence of side products due to the positive effects related to higher reaction temperature. In conclusion, the peptide is accessible by stepwise SPPS without the necessity of segment coupling.
Gesehen am 06.06.2023